2022
DOI: 10.2341/20-191-l
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Bisacryl-, Composite-, and Ceramic-resin Restorative Materials

Abstract: SUMMARY Objective: Resin-based materials used in restorative dentistry are introduced at a fast pace with limited knowledge about their properties. Comparing properties of these materials from different restorative categories is lacking but can help the clinician in material selection. This study aimed to compare mechanical properties and wear resistance of bis-acryl-, composite-, and ceramic-resin restorative materials. Methods and Materials: Bisacryl-resin (Bis-R, LuxaCrown, DMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The different chemical contents and mechanical properties of resin composites imply that many different factors influence their clinical performance [39]. SsURC, having specific color-matching mechanisms through their filler structures, can exhibit different mechanical and clinical behaviors [24].…”
Section: Introductionmentioning
confidence: 99%
“…The different chemical contents and mechanical properties of resin composites imply that many different factors influence their clinical performance [39]. SsURC, having specific color-matching mechanisms through their filler structures, can exhibit different mechanical and clinical behaviors [24].…”
Section: Introductionmentioning
confidence: 99%
“…El-Kalla Ibrahim and Garcia-Godoy Franklin in a study on the compressive and bending strength of three compomers compared to a resin-modified glass ionomer and a composite concluded that these properties in compomers were superior to the glass ionomer but inferior to the material composite [15].…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] It should be noted that the mechanical properties of resin composites can be affected by factors such as the volume and size of the fillers, 34 variations in the composition of the matrix, 35 and changes in polymerization techniques. 36,37 Fiber-reinforced composites have emerged as promising materials due to their desirable mechanical properties. 38 Glass and polyethylene fibers are commonly used as reinforcement materials in dental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Surface hardness is a crucial mechanical property that is closely associated with the durability of dental studies 31–33 . It should be noted that the mechanical properties of resin composites can be affected by factors such as the volume and size of the fillers, 34 variations in the composition of the matrix, 35 and changes in polymerization techniques 36,37 . Fiber‐reinforced composites have emerged as promising materials due to their desirable mechanical properties 38 .…”
Section: Introductionmentioning
confidence: 99%